Electrophilicities of 1, 2‐Disubstituted Ethylenes1. Issue 14 (26th March 2014) - Allgäuer, Dominik S.; Mayr, Herbert
Abstract: The kinetics of the reactions of maleic anhydride, N ‐methylmaleimide, fumaronitrile, diethyl fumarate, and diethyl maleate with pyridinium and sulfonium ylides were studied in DMSO at 20 °C. All of the reactions were found to follow a second‐order rate law, and can be described by the linear free energy relationship log  k 2 (20 °C) = s N ( N + E ), where N and s N are solvent‐dependent nucleophile‐specific parameters, and E is an electrophile‐specific parameter. The electrophilicity parameters E of the investigated acceptor‐substituted alkenes were derived from the linear correlations of (log  k 2 )/ s N vs. N, and range from –19.8 to –11.1. Abstract : The kinetics of the reactions of 1, 2‐disubstituted ethylenes with pyridinium and sulfonium ylides in DMSO were investigated photometrically. From the measured second‐order rate constants, along with the nucleophile‐specific reactivity parameters s N and N, we were able to determine the electrophilicity parameters E of the 1, 2‐disubstituted ethylenes using the relationship log  k 2 = s N ( N + E ).